Effect of nanosilica/chitosan hybrid on leaf blast and blight diseases of rice in Vietnam - Anh Tuan, Le Nghiem; Kim Dung, Lai Thi; Hien, Nguyen Quoc; Phu, Dang Van; Du, Bui Duy (Vietnam Journal of Chemistry, 2016)
Nanosilica/chitosan (NSi/CTS) hybrid material was prepared using nanosilica (32.5 nm) from rice husk ash (RHA) and chitosan (CTS), and characterized by transmission electron microscopy (TEM), Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD). The obtained NSi/CTS was used for protection of rice leaf from blast disease (Piriculariaoryzae) and blight disease (Xanthomonasoryzae). Results indicated that foliar spraying of NSi/CTS with 100 ppm NSiand150 ppm CTS were effective against blast and blight diseases on rice (Oryza spp.). The leaf blast disease index (DI) (1.49 %) and the blight DI (1.45 %) were significantly decreased compared with control of 8.08 % and 9.29 %, respectively at 14th day after the first treatment. Thus, NSi/CTS hybrid material is promising to use for controlling plant diseases, particularly for rice